SPECIFICITY OF COVID-19 INFECTION IN PATIENTS UNDERGOING MAINTENANCE HEMODIALYSIS - Brković, Voin (Medicinski podmladak, 2024)
During the Covid-19 pandemic, more than 858 million people worldwide have been infected with this virus, and over 6,4 million have died due to the infection. Similar to other infectious diseases, the implementation of personal hygiene, reduction of social contact, maintaining physical distance, and the isolation of infected patients are crucial in preventing the spread of the infection. However, the development of vaccines and active immunization are essential in preventing the spread of this highly contagious disease. Considering the health, sociological, and economic significance of the Covid-19 pandemic, various types of vaccines against the SARS-CoV-2 virus have been developed. Patients undergoing maintenance hemodialysis (HD) are at an elevated risk of SARS-CoV-2 infection primarily due to frequent comorbidities, impaired immune system function, and the inability to reduce social contacts because of the necessity to attend the dialysis center at least three times a week. The efficacy and safety of vaccines against the SARS-CoV-2 virus have been investigated and evaluated in numerous studies involving the general population, while relatively few studies have been conducted among dialysis patients. According to current knowledge, dialysis patients exhibit a weaker and slower immune response to administered vaccines compared to individuals with preserved overall renal function. On the other hand, in the cohort of patients on maintenance hemodialysis, factors such as age, diabetes, and the use of immunosuppressive therapy contributed to the development of lower antibody titers against the SARS-CoV-2 virus after active immunization. Considering the vulnerability, exposure, and reduced resistance to infections in dialysis patients, it is crucial to administer vaccination against the SARS-CoV-2 virus in these patients.